2015
DOI: 10.1186/s12936-015-1068-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of insecticide-treated mosquito nets for infants and their mothers: randomized controlled community trial in Burkina Faso

Abstract: BackgroundInsecticide-treated bed nets (ITNs) are now the main tool for malaria prevention in endemic areas. Synthetic pyrethroids are the only group of insecticides recommended by the World Health Organization for the use on ITNs. There are only few studies which have specifically investigated potential adverse effects of frequent exposure to ITNs in the vulnerable group of young infants and their mothers.MethodsThis study was nested into a large randomized controlled ITN effectiveness trial. Ninety newborns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The odds of Plasmodium infection were higher in pregnant women who have no habit of ITN usage than those who used nets always. This finding is in line with the fact that effectiveness of insecticide-treated net usage is considered as one of the most important prevention and control tools [18]. In contrast to the findings in this study, the study conducted in Burkina Faso reported no statistically significant association between asymptomatic malaria infection and insecticide-treated nets usage habit [19].…”
Section: Discussionsupporting
confidence: 77%
“…The odds of Plasmodium infection were higher in pregnant women who have no habit of ITN usage than those who used nets always. This finding is in line with the fact that effectiveness of insecticide-treated net usage is considered as one of the most important prevention and control tools [18]. In contrast to the findings in this study, the study conducted in Burkina Faso reported no statistically significant association between asymptomatic malaria infection and insecticide-treated nets usage habit [19].…”
Section: Discussionsupporting
confidence: 77%
“…The negative effects reported with the use of nets included skin irritations which could be due to non-observance of instructions before their use such as not hanging the treated nets outdoors for 24 h before usage as recommended by the MOH [ 33 ]. Skin-related symptoms such as skin eruption, pruritus and paraesthesia have been noted as side effects from the chemicals used in the treatment of ITNs but these usually last a short period of time [ 34 ]. The practice of having the net outdoors reduces such skin effects that could emerge from their use.…”
Section: Discussionmentioning
confidence: 99%
“…For each day post infection, an overall 120-mosquitoes/treatment/mosquito strain were used over 4 replicates for this second bioassay. Permethrin was chosen for this second bioassay because it is the main insecticide used on insecticide-treated bed nets (ITNs) currently mass distributed in Burkina Faso [ 2 ]. Any mosquito that died, became immobile and/or lost any part of any appendages before being transferred to the insecticide treatment was discarded according to WHOPES, 2013 requirements [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, malaria infected an estimated 212 million people around the world, killing 429,000, primarily children and pregnant women in sub-Saharan Africa [ 1 ]. Pyrethroid insecticide treated bed nets (ITNs) and indoor residual spraying (IRS) are current mainstays of mosquito control programs and have facilitated impressive reductions in the global malaria burden [ 2 ]. However, these approaches are threatened by increasing resistance to insecticides [ 3 ].…”
Section: Introductionmentioning
confidence: 99%